2019
DOI: 10.4314/acsj.v27i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype studies on ten genotypes of onion grown in Jos Plateau, Nigeria

Abstract: The large number of inter-and intra-specific differences in the genus Allium has necessitated karyotype analysis of the cultivated species, in order to describe patterns and directions of chromosomal evolution, which affects morphological differences. In this study, ten genotypes of onion (Allium cepa L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…However, the Karyotype formulas reported here in this present study conflict with those observed in other literatures. The differences that exist in Karyotype formula and asymmetric indices suggest that structural chromosomal changes might have contributed to the morphogenetic slight differences in the genotypes [27].…”
Section: Karyotype Formula Arms Ratio and Symmetry Indexmentioning
confidence: 99%
“…However, the Karyotype formulas reported here in this present study conflict with those observed in other literatures. The differences that exist in Karyotype formula and asymmetric indices suggest that structural chromosomal changes might have contributed to the morphogenetic slight differences in the genotypes [27].…”
Section: Karyotype Formula Arms Ratio and Symmetry Indexmentioning
confidence: 99%